The Expression of Self-Identity and the Internet - GÜRSOY, AYŞE BİLGE (My University, 2013)
This article examines and analyzes how gypsies express their identity on the internet, as opposed to real life. Throughout history, Gypsies, who were seen as ‘‘the different” have established tight connections with the countries and became component of the country they lived. By the help of internet, they are not ‘‘the different” or “the other” anymore and they became the citizens of McLuhan’s global village. Gypsy identity and advocacy use and focus on internet as a community platform. They express themselves comfortably and more people understand, share their problems. One of their web addresses is cingeneyiz. org (We are Gypsies. org), in which they say their first aim is to solve the problem of incomprehension between Gypsies and people living together with them. First part of this study analyses communication and self-expression of Gypsies through new technologies by giving cingeneyiz.org example, how they get in touch and organize, and the importance of hypertext, the links and e-mails are analyzed. In the second part of the article, the analysis of in- depth interview with ten gypsies (five male, five female) on their self identity is made.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Internet; self-expression; identity; gypsy